Proposition on improving environmental forensic system in China - Huilei Wang; Yuanfeng Wang (Wolters Kluwer Medknow Publications, 2017)
In the early period of China, economy developed rapidly at the cost of environment. Recently, it is generally recognized that the heavily polluted environment not only puts a brake on economic development but also paces negative impact on people' health as well as probably next decades of generations. Accordingly, the latest Environmental Protection Law revised in 2014 makes a clear-cut division of environmental responsibility and regulates stricter penalties of breaching law. As the new environmental law is enforced gradually, environmental forensic is increasingly required in the process of ascertaining facts in judicial proceedings of environmental cases. Based on the outcomes of documentary analysis for all environmental cases judged on the basis of new environmental law, it is concluded that there still exists problems in the present system of environmental forensic. Thus, this paper is aimed to make proposition on improving Chinese environmental forensic system, which involves: (i) promoting capability of EFS to handle professional questions; (ii) develop price mechanism; (iii) multidepartments cooperate to establish unifying and complete EFS system; and(iv) enhance the probative value of results of EFS. Such protocol for amending present regulation on environmental forensic is of significant importance because a quality report of environmental forensic will contribute to provide strong probative evidence of culprits' activity of releasing contaminant into environment, degree of damages for victims, and above all, causality between the behavior of public nuisance and damages.